Remotely supervised at-home delivery of taVNS for autism spectrum disorder: feasibility and initial efficacy - Black, Benjamin; Hunter, Samantha; Cottrell, Hannah; Dar, Roee; Takahashi, Nicole; Ferguson, Bradley J.; Valter, Yishai; Porges, Eric; Datta, Abhishek; Beversdorf, David Q. (Frontiers in Psychiatry, 2023)
Background Transcutaneous auricular vagus nerve stimulation (taVNS) has potential clinical application for autism spectrum disorder (ASD). At-home sessions are necessary to allow delivery of repeated sessions, and remove burden on patients for daily visits, and reduce costs of clinic delivery. Our objective was to validate a protocol for remote supervised administration for home delivery of taVNS using specially designed equipment and platform. Methods An open-label design was followed involving administration by caretakers to 12 patients with ASD (ages:7–16). Daily 1-h sessions over 2 weeks were administered under remote supervision. The primary outcome was feasibility, which was assessed by completion rate, stimulation tolerability, and confirmation of programmed stimulation delivery. The secondary measures were initial efficacy assessed by Childhood Anxiety Sensitivity Index-Revised (CASI-R), Parent Rated Anxiety Scale for Youth with ASD (PRAS-ASD), and Clinician Global Impression (CGI) scales. Sleep measures were also tracked using Cleveland Adolescent Sleep Questionnaire (CASQ). Results Across 132 sessions, we obtained an 88.5% completion rate. A total of 22 expected adverse events were reported with headache being the most common followed by transient pain, itchiness, and stinging at the electrode site. One subject dropped out of the study unrelated to the stimulation or the study. Average scores of anxiety (CASI-R, PRAS-ASD, and CGI) and sleepiness (CASQ) were all improved at the 2 week time point. While not powered to determine efficacy, benefits were suggested in this open label pilot. Conclusion Remotely supervised, proxy-administered, at-home delivery of taVNS is feasible in patients with ASD. Initial efficacy supports pursuing larger scale trials.